The Influences of Islamic Values on The Architecture of Saoraja Traditional Houses in Sidenreng Rappang Regency – South Sulawesi - Mutmainnah Mutmainnah; St. Aisyah Rahman (JICSA : Journal of Islamic Civilization in Southeast Asian, 2013)
Islamic influence in Bugis residential planning in Sidenreng Rappang Regencyis believed to have been exist since hundreds years ago. It was since the arrival of Islam inSidenrengRappang Regency around the 16thcentury. The influence can be seen inBugis traditional homes, especially the home of Bugis nobles so-called Saoraja. Bugis people also knew the pecking ordersystem that can affect the form of their homes marked with special symbols in the home. Until now, the existence ofSaorajacan still be found its track even though some have changed or renovated in terms of the forms. The object of this study is 4 (four) Saoraja representing 4 districts or villages in Sidrap Regency. They are SaorajaKulo, Lise', Bilokka and Massepe. It is interesting to be studied and hopefully it will be adopted into the concept in building Islamic modern home.